2017
DOI: 10.1097/jsa.0000000000000136
|View full text |Cite
|
Sign up to set email alerts
|

Revision Posterior Cruciate Ligament Surgery

Abstract: Successful posterior cruciate ligament (PCL) reconstruction surgery results from identification and treatment of associated pathology such as posterolateral instability, posteromedial instability, and lower extremity malalignment. The use of strong graft material, properly placed tunnels to as closely as possible approximate the PCL insertion sites, and minimization of graft bending also enhance the probability of PCL reconstruction success. In addition, mechanical graft tensioning, primary and back-up PCL gra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 17 publications
0
9
0
Order By: Relevance
“…However, a systematic review of 14 level II-V studies performed by Qi et al showed no significant differences when looking at clinical outcomes [31]. Furthermore, Fanelli et al performed a prospective randomized trial evaluating strength of repair and post-operative function with single-versus double-bundle repair and found no statistical difference as assessed by KT-1000 arthrometer testing, three knee ligament rating scales, and Telos stress radiography [32].…”
Section: Single-versus Double-bundle Reconstructionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, a systematic review of 14 level II-V studies performed by Qi et al showed no significant differences when looking at clinical outcomes [31]. Furthermore, Fanelli et al performed a prospective randomized trial evaluating strength of repair and post-operative function with single-versus double-bundle repair and found no statistical difference as assessed by KT-1000 arthrometer testing, three knee ligament rating scales, and Telos stress radiography [32].…”
Section: Single-versus Double-bundle Reconstructionmentioning
confidence: 99%
“…In addition to biomechanical evaluation, multiple studies have investigated clinical outcomes comparing single-and double-bundle methods. To date, none of these studies have provided sufficient data proving superiority of one technique over the other in regard to functional scores, patient satisfaction, or radiographic examination [31,32,34,35].…”
Section: Single-versus Double-bundle Reconstructionmentioning
confidence: 99%
“…Backup fixation is usually made on the tibial side using a button, screw and washer or suture anchor. In revision surgery, backup fixation is encouraged and often essential due to compromised bone stock [13]. Double-bundle fixation may be warranted in severe hyperextension.…”
Section: Revision Pcl Techniquesmentioning
confidence: 99%
“…PCL reconstruction has a high failure rate due to incorrect tunnel placement, selection of inappropriate surgical techniques, grafts, timing of postoperative rehabilitation, and the presence of other associated complications (infection, pain, etc.) [ 11 16 ]. The results of a previous study showed that only 50–82% of the patients who underwent PCL reconstruction were able to return to the preinjury activity level [ 17 ].…”
Section: Introductionmentioning
confidence: 99%